Prognostic value of serum glycated albumin in acute coronary syndrome patients without standard modifiable cardiovascular risk factors - Xiaoming Zhang; Yu Du; Qianyun Guo; Xiaoteng Ma; Dongmei Shi; Yujie Zhou (Diabetology & Metabolic Syndrome)
Abstract Background Glycated albumin (GA) has been demonstrated to be associated with adverse outcomes in patients with acute coronary syndrome (ACS). However, as a specific subgroup of ACS, a significant proportion of patients with ACS without standard modifiable cardiovascular risk factors (SMuRFs) are currently being identified. The prognostic value of serum GA for adverse events in such patients remains unexplored. This study aims to evaluate the prognostic value of GA in predicting adverse outcomes in patients with ACS without SMuRFs. Methods This retrospective study involved 1,140 consecutive patients who were diagnosed with ACS without SMuRFs at the Beijing Anzhen Hospital between May 2018 and December 2020 and underwent coronary angiography. Each patient was followed up for a period of 35–66 months after discharge. The primary endpoint of this study was major adverse cardiovascular and cerebrovascular events (MACCEs) that included all-cause mortality, non-fatal myocardial infarction, non-fatal ischemic stroke, and ischemia-driven revascularization. Results The average age of the study participants was 59.55 ± 10.98 years, and men accounted for 61.8%. The average GA level was 14.37 ± 2.42. The median follow-up duration was 48.3 months, during which 220 cases (19.3%) experienced MACCEs. In the fully adjusted model, with GA as a continuous variable, the hazard ratio (HR) for MACCEs in the high GA group was 1.069 (95% confidence interval (CI): 1.008, 1.133), the HR for ischemia-driven revascularization was 1.095 (95% CI: 1.021, 1.175), and the HR for all-cause mortality was 1.155 (95% CI: 1.021, 1.306), all with P values less than 0.05. Similarly, when GA was considered as a categorical variable, in the fully adjusted model, GA was associated with MACCEs, ischemia-driven revascularization, and all-cause mortality, with P values all less than 0.05. The restricted cubic spline curve showed that the relationship between GA and MACCEs was linear (p for non-linear = 0.079; p for overall association = 0.026). Furthermore, GA levels were correlated with poor prognosis in the subgroups of patients. Conclusion Serum GA might be an independent predictor of all-cause death and ischemia-driven revascularization in patients with ACS without SMuRFs.